2020
DOI: 10.1101/2020.05.13.094805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BACPHLIP: Predicting bacteriophage lifestyle from conserved protein domains

Abstract: Motivation: Bacteriophages are broadly classified into two distinct lifestyles: temperate (lysogenic) and virulent (lytic). Temperate phages are capable of a latent phase of infection within a host cell, whereas virulent phages directly replicate and lyse host cells upon infection. Accurate lifestyle identification is critical for determining the role of individual phage species within ecosystems and their effect on host evolution. Results: Here, we present BACPHLIP, a BACterioPHage LIfestyle Predictor. BACPHL… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…2012 ) to predict their lifestyle, having identified 1,161 virulent and 1,336 temperate phages. To control for the difficulties in phage lifestyle assessment, we repeated all the key analyses of this study while restricting the phage data set to the high confidence predictions of PHACTS, and also by using the alternative tool BACPHLIP ( Hockenberry and Wilke 2020 ), which uses an extensive manual curation of the data from Mavrich and Hatfull (2017) . We systematically found similar qualitative results for these controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2012 ) to predict their lifestyle, having identified 1,161 virulent and 1,336 temperate phages. To control for the difficulties in phage lifestyle assessment, we repeated all the key analyses of this study while restricting the phage data set to the high confidence predictions of PHACTS, and also by using the alternative tool BACPHLIP ( Hockenberry and Wilke 2020 ), which uses an extensive manual curation of the data from Mavrich and Hatfull (2017) . We systematically found similar qualitative results for these controls.…”
Section: Resultsmentioning
confidence: 99%
“…Using these criteria, we classified as confident 54% of the phages into 571 virulent and 780 temperate phages. Alternatively, we used BACPHLIP version 0.9.3 ( Hockenberry and Wilke 2020 ) (default parameters) to predict the lifestyle of each phage, for almost all (>99%) of the genomes. Data for the HGCF and LGCF phages were taken from ( Mavrich and Hatfull 2017 ) by matching the NCBI identifiers.…”
Section: Methodsmentioning
confidence: 99%
“…We analysed a dataset of 2487 complete phage genome sequences and used PHACTS (McNair et al 2012) to predict their lifestyle, having identified 1161 virulent and 1336 temperate phages. To control for the difficulties in phage lifestyle assessment, we repeated all the key analyses of this study while restricting the phage dataset to the high confidence predictions of PHACTS, and using the alternative tool BACPHLIP (Hockenberry and Wilke 2020), which uses an extensive manual curation of the data from (Mavrich and Hatfull 2017)).…”
Section: Resultsmentioning
confidence: 99%
“…However, this approach may obscure important differences in how natural selection operates on the translation-initiation regions of different phages. We thus predicted the lifestyle of each phage genome in the dataset using BACPHLIP [58] and noticed a striking difference between phages that are confidently predicted (≥ 0.95% probability) to be either temperate or virulent (n=143, of which 39 are temperate and 104 are virulent, Fig. 2B).…”
Section: Sequence Features In Translation-initiation Regions Differ Between Virulent and Temperate Phagesmentioning
confidence: 99%
“…We used the BACPHLIP software [58] to categorize all phage genomes in our dataset into temperate and virulent lifestyles. BACPHLIP uses genome-sequence input, determines the presence/absence of several hundred lysogeny-associated protein domains, and uses a random forest classifier return a probability of the given phage being either temperate or virulent.…”
Section: Phage Lifestyle Predictionmentioning
confidence: 99%